Expression of MDR1, LRP, BCRP and BCL-2 genes at diagnosis of childhood ALL: comparison with mrd status after induction therapy - Fedasenka, U.U.; Shman, T.V.; Savitski, V.P.; Belevcev, M.V. (Experimental Oncology, 2008)
To investigate properties of leukemic cells by sorting out children diagnosed with ALL with different response to chemotherapy based on MRD level. Methods: We used a minimal residual disease (MRD) data on day 36 obtained with 3-colour flow cytometry as a reference. In view of MRD results, we used real-time PCR to assess expression levels of multidrug resistance associated genes MDR1, LRP and BCRP, antiapoptotic gene Bcl-2 in initial samples from children diagnosed with ALL. P-gp expression and function in initial samples were analyzed by flow cytometry. Results: Briefly, medians of relative expression levels of MDR1 gene were roughly comparable and in MRD+ group came to 22.8 (0.02–26.6; n = 9) vs 24.8 (3.9–41.4; n = 10) in MRD– group. Bcl-2 gene showed tendency to higher expression levels in MRD+ group with median at 5992.9 (521.0–10362.0; n = 9) compared to 3183.6 (1947.9–6581.0; n = 10) in MRD– group. LRP gene relative expression levels were similar in both groups and came to 1934.9 (1500.7–3490.4; n = 9) and 1408.5 (665.5–2917.1; n = 10) in MRD+ and MRD– groups, respectively. The median of BCRP expression levels in MRD+ group was considerably lower than that in MRD– group, namely 76000.0 (48196.2–169230.8; n = 9) and 227967.2 (16683.7–422222.2; n = 10), respectively, but statistical analysis showed no significant difference for this parameter. Conclusion: We investigated expression of multidrug resistance genes MDR1, LRP and BCRP and antiapoptotic gene Bcl-2 in leukemic cells at diagnosis, and MRD level at the end of induction therapy, and could not find obvious relations between these parameters.